Feebly Generalized Closed Mappings - Ibraheem Resan, Dalal (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2017)
The main purpose of this paper is to study feebly generalized closed mappings , we proved several results about that by using some concepts of topological as fg-closed sets,gf-closed sets, feebly closed sets , feebly open sets , g-closed sets, feebly regular and feebly normal .